Dampak Hadits Misogini Terhadap Santri (Studi Kasus tentang Pemahaman Gender di Pesantren Salafiyah Darussalam Sumbersari Pare Kediri) - Muh Syamsuddin (Mukaddimah: Jurnal Studi Islam, 2018)
Pesantren is one of Islamic education in indonesia with traditional characteristic to explore the science of religion and practice it as a way of life. This type of education has been established since hundreds of years ago and has been extended to almost the entire Muslim society. However, lately reputation of pesantren seems questioned by some Indonesian Muslim community. The majority of Pesantren impressed away from social reality. Problems such as socialization and actualization of gender issues that are often underestimated by the Salafi students on the one hand, and perfectly natural seen by the other side.Inevitably, teaching on salafiyah’s pesantren be spotlight. For example, hadits-hadits misogyny, often enough delivered only with lectures without elaborating the contents that is inside. So understanding of the doctrines of Islam into partial and ignore the religious spirit as liberator religion. Then create the impression of gender bias in the teachings of Islam which places women in a subordinate position and marginal. So the presence of teaching hadith misogyny which written resulted in the birth of the stereotype properties are considered by society as a natural provision or provisions of God. The character and stereotypes attached to femininity or women who is really just a theory of the nature of social engineering or commonly called the social contruction, consequently become a cultural nature that the centuries-old process has resulted in the marginalization of women position.